Eksplorasi Kimia Medisinal untuk Terapi Kolesterol Tinggi : Analisis Struktur-Aktivitas dan Target Molekuler Obat - Saeful Amin; Putri Nasywa Nabilah Ma’rifatillah; Intan Permatasari; Siti Maryam (Pusat riset dan Inovasi Nasional, 2025)
Hypercholesterolemia is a significant global health problem, with a high prevalence in Indonesia. Although conventional therapies such as statins have been the mainstay of treatment, limited efficacy and side effects necessitate the development of new, more effective and selective drugs. This article explores the role of medicinal chemistry in the discovery and development of cholesterol-lowering drugs, focusing on structure-activity analysis (SAR) and molecular targets. Through structure-based approaches, compounds such as statins and PCSK9 inhibitors have been optimized to increase affinity for biological targets. In addition, exploration of new targets and formulation innovations have shown great potential in improving therapeutic efficacy. Thus, medicinal chemistry contributes significantly to providing safer and more effective therapeutic solutions for the management of hypercholesterolemia.